Strategi Bauran Promosi Agrowisata Bagus Agro Pelaga, di Desa Pelaga, Kecamatan Petang, Kabupaten Badung - ASTUTI, PUTU DEVI HAMSHA; SUARDI, I DEWA PUTU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.2, Juli 2020, 2020)
Agro Tourism Promotion Mix Strategies of Bagus Agro Pelaga in Pelaga Village, Petang Sub-District of Badung Regency Bagus Agro Pelaga is an agrotourism in North Badung. This agrotourism developed with the concept of Tri Hita Karana. This research was conducted with the aim to find out internal and external factors of Bagus Agro Pelaga. Determine alternative strategies and priority strategies for Bagus Agro Pelaga. The research methods used to achieve these objectives, namely descriptive analysis, SWOT analysis and QSPM. This study uses informants selected through the purposive sampling method with applicable terms and conditions. The resulting strategic priorities for Bagus Agro Pelaga include implementing cooperation with the local government, local communities, travel agents and sister partnerships. In addition, Bagus Agro Pelaga can also carry out market diversification by highlighting on-farm, off-farm and out-farm activities.